The Lives of Hostages and their Influence on the Conversion and Acculturation of Livonia and Prussia during the Baltic Crusades in the 13th Century - Kristjan Kaljusaar (Acta Historica Universitatis Klaipedensis, 2016)
Chronicles of the 13th-century Crusades in Livonia and Prussia are full of descriptions of the Catholic conquerors demanding hostages from local elites, but the fate of these hostages and the influence they may have had on the processes of religious conversion and societal change in the east Baltic has attracted little attention. This paper explores the lives of Livonian and Prussian hostages, and argues that they may have functioned as vessels of acculturation, who furthered the Christianisation and ‘Europeanisation’ of their homelands, and cemented new power relations and world-views.